HBR's 10 Must Reads for CEOs - Review, Harvard; Reeves, Martin; Love, Claire; Tillmanns, Philipp; Kotter, John (Ascent Audio, 2019)
As CEO, you set the vision, the strategy, and the tone of your organization. You establish priorities, anticipate and address challenges, champion and lead change efforts, set people up for success, and manage risk. Though you may have a great senior executive team and a top-flight board, the success of your organization depends on your leadership. We've combed through hundreds of Harvard Business Review articles and selected the best ones to help you toggle between long- and short-term views, manage risk and innovation, and cultivate productive relationships with your staff and your board. This book will inspire you to: navigate the changing global business environment; customize your company's strategy to the environment you're working in; attract, engage, and retain the best talent; anticipate and address legislative and regulatory issues; sharpen your awareness of the tactical and soft skills you need to lead; adopt a founder's mindset and build new offerings, move into new markets, and create next-generation solutions; and manage and build relationships with your board-and your shareholders.
Online resource; Title from title page (viewed December 10, 2019)
Keywords: Business; Affaires; businesses (business enterprises); Audiobooks